STRATEGI BERTAHAN HIDUP PEREMPUAN PENJUAL BUAH-BUAHAN DI PASAR RAYA PADANG KECAMATAN PADANG BARAT KOTA PADANG PROVINSI SUMATERA BARAT - Irwan, Irwan; Fitlayeni, Rinel; Marleni, Marleni (Pendidikan Sosiologi, 2013)
This research is motivated by the involvement of women in the public sector that has limited resources and access. The effect is the options of range effort that was involved in a one commodity selling fruits. Problems that are often encountered women fruit sellers, among others, there are some pieces that are crop season pales in season then an increase in their economies. Another obstacle perishable fruit consequently is lowered the price of fruit. These conditions force and require women to have a variety of strategies to maintain viability to meet the needs of the family. While the purpose of the study to describe factors that encourage women to choose of selling Â their fruits and describe survival strategies of women fruit sellers to overcome the problem of incoming to meet family needs. The theory that is used is the structural functional by Talcot Parson, it is known as carabao AGIL scheme. This research is qualitative descriptive study to develop the type of problem being investigated. Techniques of collecting data are through observation, interview, and documentation. Based on the results it can be concluded: 1. Factors of women choose to sell fruits are, a). economic factors that women choose to sell fruit because no large capital needs. In addition, the Â needs of families that encourage women to choose this business. b). social factors and cultural heritage, are the efforts of parents and their relation with fruit growers c). seasonal factors, d). educational factors, it is Â caused women fruiterer average low education. 2. A strategies that women employ fruiterer to survive in a family which are a). implementing a dual income b). reducing of spending in household in c). doing bussines with growers of fruit or fruit agent d). arisan e) changing the type of fruit depanding on the season periods fruits f). changing the type of the things that solid.